2018
DOI: 10.1177/1475725718757171
|View full text |Cite
|
Sign up to set email alerts
|

Learning Scientific Explanations by Means of Worked Examples – Promoting Psychology Students’ Explanation Competence

Abstract: The aim of this study is to investigate whether worked examples are effective in fostering psychology students' explanation competence. Explanation competence is a context-specific cognitive disposition that enables a person to construct a causal model of an observable psychological phenomenon by drawing on psychological theories. We set up a training intervention using worked examples to demonstrate how the observed psychological phenomenon (e.g., cognitive dissonance) is represented in an explanation. Instru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…Thus, this type of instructional element might help pre-service teachers to more easily represent scientific knowledge cognitively and therefore to more adequately apply it to technology-enhanced teaching situations. In the context of evidence-based reasoning, first evidence from Klopp and Stark (2018) indicates that learning from worked examples might enhance pre-service teachers' knowledge about relevant processes (form quality) and the adequate use of scientific knowledge (content quality) when reasoning about technology-enhanced teaching situations. We therefore decided to implement and investigate the effectiveness of these two instructional approaches in the context of TPACK-PV development.…”
Section: Fostering Pre-service Teachers' Tpack-pvmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, this type of instructional element might help pre-service teachers to more easily represent scientific knowledge cognitively and therefore to more adequately apply it to technology-enhanced teaching situations. In the context of evidence-based reasoning, first evidence from Klopp and Stark (2018) indicates that learning from worked examples might enhance pre-service teachers' knowledge about relevant processes (form quality) and the adequate use of scientific knowledge (content quality) when reasoning about technology-enhanced teaching situations. We therefore decided to implement and investigate the effectiveness of these two instructional approaches in the context of TPACK-PV development.…”
Section: Fostering Pre-service Teachers' Tpack-pvmentioning
confidence: 99%
“…physics: van Gog et al, 2006;design: Rourke & Sweller, 2009), as illustrated in the positive effect on students' learning outcome determined in a meta-analysis by Crissman (2006). In addition, in the context of evidence-based reasoning, Klopp and Stark (2018) found that studying worked examples compared to studying non-relevant texts increased pre-service teachers' knowledge about the formal quality and the quality of pre-service teachers' explanations in terms of content quality.…”
Section: Learning From Worked Examples As a Means To Foster Form And ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In this contribution, the learning-domain represents knowledge about argumentation errors whereas the exemplifying-domain represents knowledge about the content that is used to demonstrate the errors. Doublecontent examples have been successfully used in research on fostering argumentation competence (e.g., Schworm and Renkl, 2007;Hefter et al, 2014;Klopp and Stark, 2018).…”
Section: Fostering Argumentation Competence Through Learning From Advmentioning
confidence: 99%
“…In this contribution, the learning-domain represents knowledge about argumentation errors whereas the exemplifying-domain represents knowledge about the content that is used to demonstrate the errors. Doublecontent examples have been successfully used in research on fostering argumentation competence (e.g., Schworm and Renkl, 2007;Hefter et al, 2014;Klopp and Stark, 2018).…”
Section: Fostering Argumentation Competence Through Learning From Advmentioning
confidence: 99%